2010
DOI: 10.1128/jcm.00370-10
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Typing by Integration of Genome Sequencing Data in a Large Tuberculosis Cluster

Abstract: To investigate whether genome sequencing yields more useful markers than those currently used to study the epidemiology of tuberculosis, it was applied to three Mycobacterium tuberculosis isolates of the Harlingen outbreak. Our findings suggest that single nucleotide polymorphisms can be used to identify transmission chains in restriction fragment length polymorphism clusters.Molecular typing contributes significantly to our understanding of the epidemiology of tuberculosis. A variety of genetic markers, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
73
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 23 publications
2
73
0
Order By: Relevance
“…One way to address this challenge is whole-genome sequencing (WGS), which provides the highest discrimination power and where homoplasy is not an issue (7). In recent years, with the development of high-throughput next-generation sequencing technology, several studies have applied WGS to reconstruct transmission chains between VNTR-defined cluster cases (15,22,40), and some clustered strains defined by traditional molecular genotyping methods were identified as distantly related isolates (37). However, because of the relatively high cost and the complexity of data analysis, the application of this technology to study the molecular epidemiology of M.tuberculosis will be limited for some time, especially in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…One way to address this challenge is whole-genome sequencing (WGS), which provides the highest discrimination power and where homoplasy is not an issue (7). In recent years, with the development of high-throughput next-generation sequencing technology, several studies have applied WGS to reconstruct transmission chains between VNTR-defined cluster cases (15,22,40), and some clustered strains defined by traditional molecular genotyping methods were identified as distantly related isolates (37). However, because of the relatively high cost and the complexity of data analysis, the application of this technology to study the molecular epidemiology of M.tuberculosis will be limited for some time, especially in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that not all cases in DNA fingerprint clusters have epidemiological links with other cases in the cluster (4,5). Moreover, epidemiological links have been found between cases caused by bacteria with slightly different DNA fingerprints (6). Clustering results among cases in the immigrant population especially should be interpreted with caution (7,8), as isolates from these patients often belong to genetically compact strain lineages predominating in the countries of origin (9,10,11,12).…”
mentioning
confidence: 99%
“…IS6110 RFLP typing identified the so-called Harlingen cluster in The Netherlands, which is, with over 100 tuberculosis patients identified since 1993, one of the largest tuberculosis clusters found in the country (16,17,25,26). The initial outbreak took place in the harbor town of Harlingen, but the strain soon spread through The Netherlands.…”
mentioning
confidence: 99%
“…This locus is a member of the bacterial clustered regularly interspaced short palindromic repeats (CRISPR), which provides acquired immunity against viruses and plasmids (13). The DR locus is a hot spot region for integration of IS6110 insertion sequences (11,20,34), and several preferential insertion sites in this genomic region have been identified (22,34).IS6110 RFLP typing identified the so-called Harlingen cluster in The Netherlands, which is, with over 100 tuberculosis patients identified since 1993, one of the largest tuberculosis clusters found in the country (16,17,25,26). The initial outbreak took place in the harbor town of Harlingen, but the strain soon spread through The Netherlands.…”
mentioning
confidence: 99%
See 1 more Smart Citation